2020
DOI: 10.29252/jafm.13.03.30618
|View full text |Cite
|
Sign up to set email alerts
|

Universal Method for Determination of Leakage in Labyrinth Seal

Abstract: This paper presents calculation model enabling determination of the leakage rate in labyrinth seals. Described model is based on the Saint-Venant equation. It includes a new type of flow coefficient, which was determined based on experimental tests and described depending on the Reynolds number and the radial clearance. The structure of this calculation model can be applied to determine the leakage rate in straight through, staggered labyrinth seals as well as with various number of clearances. This model enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Geometries of straight through labyrinth seals used so far usually have the pitchchamber height ratio approximately equal to unity (LP/H≈1). From the paper [15] it arises that leakage in straight through seals is significantly lower when the geometry of the seal is characterized by the parameter (LP-B)/H approximately equal to 0.5. The value of the parameter (LP-B)/H is verified for the initial geometry.…”
Section: Choice Of the Initial Geometry Of The Straight Through Seal For The Methods Of Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Geometries of straight through labyrinth seals used so far usually have the pitchchamber height ratio approximately equal to unity (LP/H≈1). From the paper [15] it arises that leakage in straight through seals is significantly lower when the geometry of the seal is characterized by the parameter (LP-B)/H approximately equal to 0.5. The value of the parameter (LP-B)/H is verified for the initial geometry.…”
Section: Choice Of the Initial Geometry Of The Straight Through Seal For The Methods Of Optimizationmentioning
confidence: 99%
“…This phenomenon is particularly intensive in straight through seals where the expanding gas stream flows through the whole chamber length with a high velocity. The degree of seal wear has considerable impact on the leak-tightness of the seal [14][15][16]. Leakage of the seal depends on such features of the seal geometry as pitch, length, and height of the chamber [17][18][19][20].…”
Section: Fig 3 Vectors Of Velocity Fields In a Chosen Segmentmentioning
confidence: 99%
“…The Saint-Venant equation was modified and used to calculate the leakage rate through the labyrinth seals. The model included a new form of flow coefficient that was calculated using experimental data and defined in terms of Reynolds number and radial clearance (Joachimiak 2020) (Joachimiak and Krzyśłak 2019).…”
Section: Interlobe Clearance Leakages In Twin-screw Compressormentioning
confidence: 99%
“…Analyses presented in this paper were inspired by research on the flow coefficient, which has been partly described in [4]. During this research, we observed the step character of the flow coefficient change.…”
Section: Introductionmentioning
confidence: 96%